Building networks to harness innovation synergies: Towards an open systems approach to sustainable development - Rajah Rasiah (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Open innovation has become a popular approach, especially since 2003, as people began purposively managing, evolving and harnessing knowledge flows across organizational boundaries but through increasing connections with systemic knowledge nodes relevant to the innovation process. The creation and appropriation of such knowledge has evolved rapidly with digitalization and the proliferation of broadband networks. Individuals, firms and organizations now connect and coordinate to support innovations openly across innovation systems. This paper proposes an open systems model with institutional underpinnings to not only quicken knowledge flows and expand the networks to a wider range of socioeconomic agents, but also for their inclusive participation in shaping the processes of achieving sustainable development through environmental greening and egalitarian balancing of society. In doing so, using examples, the paper focuses on developments since Schumpeter's ground-breaking exposition of innovation to explain how individuals, firms, farms and organizations can participate actively in open innovation networks to connect productively with the critical knowledge nodes in society.
Keywords: 650; egalitarian society; environmental greening; open innovation; sustainable development; systems approach